The Anti-helminthic Compound Mebendazole Has Multiple Antifungal Effects against Cryptococcus neoformans - Joffe, Luna S.; Schneider, Rafael; Lopes, William; Azevedo, Renata; Staats, Charley C.; Kmetzsch, Lívia; Schrank, Augusto; Del Poeta, Maurizio; Vainstein, Marilene H.; Rodrigues, Marcio L. (Frontiers in Microbiology, 2017)
Cryptococcus neoformans is the most lethal pathogen of the central nervous system. The gold standard treatment of cryptococcosis, a combination of amphotericin B with 5-fluorocytosine, involves broad toxicity, high costs, limited efficacy and worldwide availability. Although the need for new antifungals is clear, drug research and development (R&D) is costly and time-consuming. Thus, drug repurposing is an alternative to R&D and to the currently available tools for treating fungal diseases. Here we screened a collection of compounds approved for use in humans seeking for those with anti-cryptococcal activity. We found that benzimidazoles class is a broad class of chemicals inhibiting C. neoformans growth. Mebendazole and fenbendazole were the most efficient antifungals showing in vitro fungicidal activity. Since previous studies showed that mebendazole reaches the brain in biologically active concentrations, this compound was selected for further studies. Mebendazole showed antifungal activity against phagocytized C. neoformans, affected cryptococcal biofilms profoundly and caused marked morphological alterations in C. neoformans, including reduction of capsular dimensions. Amphotericin B and mebendazole had additive anti-cryptococcal effects. Mebendazole was also active against the C. neoformans sibling species, C. gattii. To further characterize the effects of the drug a random C. gattii mutant library was screened and indicated that the antifungal activity of mebendazole requires previously unknown cryptococcal targets. Our results indicate that mebendazole is as a promising prototype for the future development of anti-cryptococcal drugs.